The Influence Of Leadership, Incentives and Work Discipline at PT. Sinar Mutli Sepadan Finance Bengkulu City - Maldani, Dhiki; Subandrio , Subandrio (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the influence of leadership, incentives and work discipline on employee performance at PT. Sinar Mutli Sepadan Finance Bengkulu City. This type of research is a type of quantitative descriptive research, the object of this research is the employees of PT. Sinar Multi Sepadan Finance Bengkulu City, which is precisely located on Jl. Salak Raya, Bengkulu City, Bengkulu. The sampling method uses a non probability technique, namely accidental sampling. The number of respondents in this study were 160 people. Methods of data collection using a questionnaire. Data analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Test, namely t test and f test. The results of this study can be concluded that the variable Leadership has a positive effect on Employee Performance, Incentives have a positive effect on Employee Performance, Work Discipline has a positive effect on Employee Performance, and Leadership, Incentives and Work Discipline together have a significant effect on Employee Performance at PT. Sinar Mutli Sepadan Finance Bengkulu City.